Peran Filsafat Teknologi dalam Meningkatkan Kualitas Teknologi Pendidikan di Era Disrupsi - Amelia Putri W; S, Annisa Anastasia; Cahyani, Karina; Herlambang, Yusuf Tri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The role of technology in life is very important, including in education, where technology is used to improve learning efficiency according to developments, situations, and needs of society. Humans will feel the benefits of this technological role if they can adapt and accept change. This study aims to determine the role of technology philosophy in improving the quality of educational technology in the era of disruption. The method used is library research. This literature study is a method that involves collecting data by investigating and understanding theories contained in various literature related to the topics discussed in this article. The source of this research data is in the form of research articles, books, and other relevant references. The results of data analysis show that the quality of educational technology and the role of philosophy in guiding its use can help achieve the goal of education that is more inclusive, competitive, and relevant to the needs of society. Quality education in an era of disruption will help create a society that is skilled, knowledgeable, and ready to contribute to a world full of technological and social changes